(untitled) (Veterinary Science, 2022)
The major histocompatibility complex (MHC) in chickens (Gallus gallus) is located on a micro chromosome, 16 of the avian genome. in other species, it has a strong association with genetic resistance to diseases. This multigene trait is particularly desirable for the selection of this species, in particular for its relation to animal welfare. This work aims to review the knowledge on the analysis of the variability of MHC-B in chickens and its analysis methodologies and a synthesis of the work carried out in chickens Campero INTA